2016
DOI: 10.7189/jogh.06.010405
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the validity of indicators of the quality of maternal and newborn health care in Kenya

Abstract: BackgroundThe measurement of progress in maternal and newborn health often relies on data provided by women in surveys on the quality of care they received. The majority of these indicators, however, including the widely tracked “skilled attendance at birth” indicator, have not been validated. We assess the validity of a large set of maternal and newborn health indicators that are included or have the potential to be included in population–based surveys.MethodsWe compare women’s reports of care received during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
132
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(152 citation statements)
references
References 19 publications
(26 reference statements)
12
132
6
Order By: Relevance
“…EN-BIRTH is the first large study to assess validity of newborn and maternal care indicators in routine data systems, doing so at very large scale (>20 000 observed births) across three countries with a high-burden of mortality. Previous maternal and newborn indicator validation studies have focused on testing the validity of women' s self-report method, used in population-based household surveys [25,[46][47][48]64].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EN-BIRTH is the first large study to assess validity of newborn and maternal care indicators in routine data systems, doing so at very large scale (>20 000 observed births) across three countries with a high-burden of mortality. Previous maternal and newborn indicator validation studies have focused on testing the validity of women' s self-report method, used in population-based household surveys [25,[46][47][48]64].…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the reported indicator to an external data source "gold standard" is recommended [45]. Previous validation studies have mainly focused on population-based intervention coverage indicators for use in household surveys [25,[46][47][48]. Observational studies to determine accuracy of facility registers in high burden settings have typically focused on outcome indicators [29].…”
Section: Viewpoints Research Theme 5: Measuring Coverage Of Essentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the systemic issues influencing quality of care in Egypt [58] and documented substandard intrapartum practices [34,35], tools that can capture better measures of quality of care during and after delivery should be developed. However, such data and indicators are unlikely to be collected from women themselves, due to poor validity [64][65][66][67]. Finally, it was not possible to assess whether women in public hospitals were in a public or a paying/private section.…”
Section: Limitationsmentioning
confidence: 99%
“…Measurement errors in PNC contact also come from the recall interviews with mothers. Several studies have shown recall issues from mothers on maternal and newborn health care questions [9][10][11]. A qualitative study among women in Ghana revealed that mothers can only recall checks that were easily observed and for which the health provider explained the services being provided to the mothers.…”
Section: Additional Materialsmentioning
confidence: 99%